The effects of oxytocin on social reward learning in humans. (28th October 2013) - Clark-Elford, Rebecca; Nathan, Pradeep J.; Auyeung, Bonnie; Voon, Valerie; Sule, Akeem; Müller, Ulrich; Dudas, Robert; Sahakian, Barbara J.; Phan, K. Luan; Baron-Cohen, Simon
Abstract: It has been hypothesised that the mechanisms modulating social affiliation are regulated by reward circuitry. Oxytocin, previously shown to support affiliative behaviour and the processing of socio-emotional stimuli, is expressed in areas of the brain involved in reward and motivation. However, limited data are available that test if oxytocin is directly involved in reward learning, or whether oxytocin can modulate the effect of emotion on reward learning. In a double-blind, randomised, placebo-controlled, within-group study design, 24 typical male volunteers were administered 24 IU of oxytocin or placebo and subsequently completed an affective reward learning task. Oxytocin selectively reduced performance of learning rewards, but not losses, from happy faces. The mechanism by which oxytocin may be exerting this effect is discussed in terms of whether oxytocin is affecting identity recognition via affecting the salience of happy faces. We conclude that oxytocin detrimentally affects learning rewards from happy faces in certain contexts.